214 Noninvasive Monitoring of Immunotherapeutic Responses in Glioblastoma Using Novel Imaging Techniques. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Antonios, Joseph P; Soto, Horacio; Everson, Richard G; Wang, Anthony C; Bethel, Jacob; Radu, Caius; Ellingson, Benjamin; Phelps, Michael; Cloughesy, Timothy F; Prins, Robert M; Liau, Linda M
Abstract: INTRODUCTION: Contrast-enhanced MRI has been the mainstay for the assessment of treatment response and progression monitoring of glioblastoma (GBM). However, its utility in the advancing immunotherapeutic field has been limited. Current imaging techniques have demonstrated limited utility in differentiating tumor progression from pseudoprogression. We sought to develop a noninvasive imaging technique that could allow us to distinguish between these 2 conditions and inform appropriate clinical management of GBM patients. We hypothesized that PET probes specific for deoxycytidine kinase (dCK), an inflammatory marker, could differentiate immune responses from other sources of contrast enhancement on MR imaging. METHODS: Orthotopic gliomas were established intracranially in syngeneic, immunocompetent mice. Following this, mice were treated with dendritic cell (DC) vaccination, PD-1 mAb blockade, and/or CSF-1R inhibitor drug (PLX3397). Mice were then imaged using [18F]-FAC PET/CT and MRI with intravenous contrast. The ratio of MRI contrast enhancement to PET probe uptake, termed the immunotherapeutic response index, delineated specific regions of immune inflammatory activity. RESULTS: Intratumoral uptake of probe in mice treated with combination therapy, with a median uptake of 6.62% ID/g, was significantly elevated over uptake in control untreated mice (0.54%ID/g) ( P  < .01). PET probe uptake directly correlated with postmortem FACS-based quantification of tumor-infiltrating lymphocytes (TIL) in the respective treatment groups. When compared to minimal lymphocyte infiltration in control untreated mice, the combination therapy group had a median TIL count of 5.5 × 106 (3.2 × 104 TIL count) ( P  < .001). CONCLUSION: These findings identify a noninvasive imaging modality for monitoring of intracranial immune responses following immunotherapeutic treatment. We anticipate that these techniques can be directly applied to the clinical setting and facilitate immune monitoring in the glioblastoma patient population.